Cataract surgery and non-attendance: RCT to determine the effect of a SMS reminder system and financial impact in a developing country - Malherbe, Lodewicus Francois (Division of Ophthalmology, 2018)
AIMS: Missed cataract surgical appointments are an important cause of inefficiency, with delays in appropriate treatment, loss of continuity of care, and wasted resources. This study was conducted to determine if an SMS reminder system will reduce the failure to attend (FTA) rate by our patients who are booked for cataract surgery. METHODS: A randomised controlled trial was conducted at Groote Schuur Hospital between June 2015 and June 2016. Eligible patients were randomised into one of two study groups: either the "NO reminder control group "or the "SMS reminder intervention group". Patients in the SMS reminder group were entered into a secure web platform from which the automated SMS reminder system dispatched an SMS reminder one month, four days and one day pre-operatively between 10am and 12am. The message contained the following: "Dear "Mr/Mrs name", this is to confirm your cataract surgery at Groote Schuur Hospital, booked for "date". Please phone 021 404 3541 if any queries." RESULTS: 234 patients were enrolled into this study, and 15 patients were excluded. Of the remaining 219 patients, 111 were randomised into the NO reminder group (control) and 108 into the SMS reminder group (intervention). SMS reminders reduced the FTA rate by 52.6% from 11.7% to 5.6% (p=0.11). Transport problems were identified as the most common reason for non-attendance. CONCLUSION: An SMS reminder system aids in the reduction of non-attendance for booked cataract surgery. With an estimated cost of only 54 cents for three SMS reminders, this affordable intervention results in an improved efficiency of clinical service delivery.